Peran Pemerintah Daerah dalam Mencegah Pembuangan Limbah Industri Secara Illegal - Sri Yunita; Mita Agresia Gurning; Nazwa Azzahra; Eka Guspi Anti Siregar; Tien Parsaulian Hutagalung; Cindy Monalisa Sihombing (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
In carrying out economic development in Indonesia, it has an impact on the rampant environmental damage which means the rampant environmental crimes that occur in Indonesia. Basically, these development activities contain the risk of environmental pollution and damage. Lack of supervision of environmental management permits by authorized agencies, law enforcement officers who are less than optimal in enforcing environmental law and weak criminal sanctions and compensation applied to business actors who violate, cause a lack of deterrent effect on business actors who violate. In addition, the desire of business actors who only prioritize profit and do not care about environmental recovery by ignoring the management of solid waste of Hazardous and Toxic Materials (B3) which can have a fatal impact on the environment. Management of hazardous and toxic waste (B3) in Indonesia is guided by Government Regulation Number 101 of 2014 concerning Management of Hazardous and Toxic Waste (B3) and Law Number 32 of 2009 concerning Environmental Protection and Management. B3 waste is a waste or waste whose nature and concentration contain toxic and hazardous substances so that directly or indirectly it can damage the environment, disrupt health, and threaten the survival of humans and other organisms. B3 waste is not only produced from industrial activities but household activities can produce several types of this waste. The method used is normative legal research by examining the regulations and laws that regulate it. This study aims to determine the relationship between positive legal regulations and the problem of B3 waste and how to overcome this B3 waste so that the environment is maintained.